2019
DOI: 10.1007/s10683-019-09626-x
|View full text |Cite
|
Sign up to set email alerts
|

Fairness considerations in joint venture formation

Abstract: Using a series of laboratory experiments in the context of bilateral bargaining over whether and how to engage in a joint venture, this paper shows that fairness concerns result in failures to undertake profitable joint production opportunities. We find that framing an opportunity as an employment relationship rather than as a partnership significantly reduces these inefficiencies and increases subjects' welfare. Consistent with the theoretical model developed in the paper, text analysis and a follow-up experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Our work could be the starting point for further research on one-to-many bargaining. One possible direction is how the bargaining is contextualized; previous research has shown that the way a relationship is described can affect fairness perceptions in bargaining behavior in the relationship [62]. Also, the way a bargaining position was obtained (e.g., by the bargainers' own previous performance, as opposed to exogenous assignment as in our experiment) might lead to the bargainer developing entitlements [63] that could affect behavior.…”
Section: Concluding Discussionmentioning
confidence: 90%
“…Our work could be the starting point for further research on one-to-many bargaining. One possible direction is how the bargaining is contextualized; previous research has shown that the way a relationship is described can affect fairness perceptions in bargaining behavior in the relationship [62]. Also, the way a bargaining position was obtained (e.g., by the bargainers' own previous performance, as opposed to exogenous assignment as in our experiment) might lead to the bargainer developing entitlements [63] that could affect behavior.…”
Section: Concluding Discussionmentioning
confidence: 90%
“…The output sharing model from Gill and Stone (2015) shows that fairness concerns can lead to significant inefficiencies in team members' efforts to choose. Hossain et al (2019) found through an experiment that when one party felt that the profit distribution was unfair, cooperation would often fail. These conclusions were arrived at using symmetric information.…”
Section: Related Literaturementioning
confidence: 99%